FRI0011 Mycophenolic Acid Synergizes with Lipopolysaccharide To Induce Interleukin (IL)-1β Release via Activation of Caspase-1 and Protects MRL/LPR Mice against Mortality Induced by Endotoxemia. (15th July 2016) - Huang, X.; He, Y.; Zhuang, J.; Sun, E.
Abstract : Background: Mycophenolate mofetil (MMF), which inhibits T and B lymphocyte proliferation, is widely used to treat a variety of autoimmune diseases, such as systemic lupus erythematosus (SLE) and lupus nephritis (LN)[1]. Several studies have reported that in lupus nephritis induction therapy, MMF was more effective than intravenous cyclophosphamide (CYC) with a more safety profile [2], but the mechanism is still unclear. We are the first to show that mycophenolic acid (MPA), the active metabolite of MMF, in association with lipopolysaccharide (LPS), is able to promote the secretion of interleukin (IL)-1β[3], which contradicts the traditional conception that immunosuppressants inhibit the secretion of inflammatory factors. This may be related to patients who are treated with MMF exhibiting better clinical outcomes and a lower incidence of infection than patients treated with CYC. Objectives: To investigate the mechanism and significance of MPA synergizing with LPS to induce IL-1β release. Methods: Undiluted human blood, THP-1 cells or monocytes was stimulated with LPS and treated with or without MPA, and the supernatant IL-1β was detected by ELISA. The intracellular protein levels of THP-1cells were measured by Western blot. MRL/lpr mice were treated with saline, MMF or CYC for 2 months, then given an intraperitoneal (i.p.) injection of LPS or saline, the effect, survival and cytokines were observed. Results: We found that MPA alone failed to induce IL-1β, whereas MPA synergized with LPS to increase IL-1β in a dose-dependent manner. MPA did not affect the intracellular p-p65 and pro-IL-1β protein levels. However, MPA augmented LPS-induced IL-1β release by activation of NLRP3 inflammasome (Fig. 1 A, B). Ac-YVAD-cmk, the inhibitor of caspase-1, blocked the activation of caspase-1 and subsequently attenuated IL-1β secretion. Both MMF and CYC can prevent the development of LN in MRL/lpr mice. Only MMF can protect mice from mortality after LPS-induced septic shock (Fig. 1 C). Conclusions: MPA synergizes with LPS to induce IL-1β release depended on the activation of caspase-1 rather than the enhanced production of pro-IL-1β. MMF protects mice against mortality induced by LPS. These findings suggest that patients immunosupressed with MMF may have overly activated caspase-1, which causes a more sensitive host defense response to invading germs by promoting the induction of IL-1β. References: Conti, F., et al., Mycophenolate mofetil in systemic lupus erythematosus: results from a retrospective study in a large monocentric cohort and review of the literature. Immunol Res, 2014. 60(2–3): p. 270–6. Ginzler, E.M., et al., Mycophenolate mofetil or intravenous cyclophosphamide for lupus nephritis. N Engl J Med, 2005. 353(21): p. 2219–28. Liu, Z., et al., Evaluating the effects of immunosuppressants on human immunity using cytokine profiles of whole blood. Cytokine, 2009. 45(2): p. 141–147. Acknowledgement: This work was supported by National Natural Science Foundation of China(81501417). Xuechan Huang and Yi He contribute equally to this study. Corresponding author is Erwei Sun. Disclosure of Interest: None declared